Prepectoral Breast Reconstruction Without the Use of Acellular Dermal Matrix: A 3-Year Review. (May 2022) - Poveromo, Luke P.; Franck, Philipp; Ellison, Angela; Janhofer, David E.; Asadourian, Paul A.; Otterburn, David M.
Abstract : Introduction: Acellular dermal matrix (ADM) is frequently used during prepectoral tissue expander–based breast reconstruction. However, there has been a paucity of literature describing the experience of prepectoral reconstruction without the accompanying use of ADM. We seek to highlight our institutional experience with immediate prepectoral tissue expander placement without the use of ADM in breast reconstruction. Methods: A retrospective, single-institution review of patient records was performed to identify all patients who underwent either skin sparing or nipple-sparing mastectomy with immediate tissue expander placement without the use of ADM. Demographics including age, body mass index, comorbidities, history of smoking or steroid use, perioperative radiation or chemotherapy, intraoperative details, and complication profiles during the tissue expander stage were retrospectively collected and analyzed. At the time of tissue expander placement, all mastectomy flaps were evaluated clinically and with indocyanine green laser angiography. Postoperative outcomes were tracked. Results: Between 2017 and 2020, 63 patients (for a total of 108 breasts) underwent either skin sparing (16%) or nipple-sparing mastectomy (84%) with immediate prepectoral tissue expander without ADM placement. Fourteen percent of breasts developed postoperative cellulitis, 19% of breasts developed skin compromise, and 5% required a postoperative revisional procedure that did not result in immediate expander explant. There was a 13% (n = 14 breasts) explant rate occurring at a mean time of 74 days. Of those breasts that developed skin compromise, 45% went on to require eventual explant. Patients in the study were followed for an average of 6.3 months. Conclusions: Immediate prepectoral breast reconstruction using tissue expanders without ADM offers a viable alternative to established reconstructive paradigms. The major complication rate for prepectoral reconstruction without the use of ADM (17%) was found to be comparable with our historical subpectoral tissue expander reconstruction with ADM use. Tissue expander explant rates were also comparable between the prepectoral without ADM (13%) and the subpectoral with ADM cohorts. These preliminary data suggest that immediate breast reconstruction with tissue expander placement without accompanying ADM is viable alternative in the breast reconstructive algorithm.